Thursday
March 23, 2017

Post a New Question

Posted by on Saturday, June 11, 2011 at 11:09pm.

4(7x-1)=3(2x+1)-4(x+6) x=?

  • Algebra - , Saturday, June 11, 2011 at 11:10pm

    Jon, Anne, Tom, Jonah, Sari --

    I solved your first two problems. Now it's your turn. We'll be glad to check your answers.

  • Algebra - , Sunday, June 12, 2011 at 7:59am

    just distribute, then combine like terms: if it helps break it down: 4(7x),4(-1)=3(2x),3(1)=-4(x),-4(6) so then you have: 28x-4=6x+3-4x-24, then just combine like terms, you goal is to isolate the variable

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question